GANGGUAN KELEKATAN SEBAGAI PENCETUS TERJADINYA SKIZOFRENIA : TINJAUAN PUSTAKA - SITANGGANG, AMITA ROULI PURNAMA; ARDANI, I GUSTI AYU INDAH; LESMANA, COKORDA BAGUS JAYA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Schizophrenia is one of the non-fatal diseases that result in a heavy burden for patients, society, and the government, with a prevalence rate of 0.5-1% of the world's population, or more than 20 million people worldwide. In Indonesia, according to the Ministry of Health of the Republic of Indonesia in 2019, it is estimated that there are 450,000 people with mental disorders, including schizophrenia. Although the exact cause of schizophrenia is not yet known, several factors are suspected to influence the occurrence of schizophrenia, one of which is emotional trauma due to attachment disorders. Attachment theory offers a conceptualization of the formation of emotional bonds, social functions, and emotional regulation that can help explain the occurrence of mental disorders, including schizophrenia. A literature review was conducted through data sources such as PubMed, Google Scholar, Medline, and PsycINFO to search for data on attachment theory, attachment disorders, and schizophrenia. Attachment disorders are experienced in the early stages of development in the form of trauma. Trauma experienced in the early stages of development, such as negative events, neglect, or inadequate caregiving, is a factor that can affect brain development, leading to changes in neuroendocrine function, resulting in disturbances in emotional regulation and cognitive function. There is a decrease in the ability to identify and understand one's own and others' mental states, such as beliefs, emotions, and intentions, known as